Sterile line Dexiang074A enhances drought tolerance in hybrid rice - Li, Gengmi; Zhang, Tao; Yang, Li; Qin, Jian; Yang, Qianhua; Cao, Yingjiang; Luo, Jing; Li, Xiangzhao; Gao, Lei; Chen, Qian; He, Xingping; Huang, Yong; et al. (Frontiers in Plant Science, 2023)
Heterosis has been widely used in rice breeding, especially in improving rice yield. But it has rarely been studied in rice abiotic stress, including the drought tolerance, which is becoming one of the most important threaten in decreasing rice yield. Therefore, it is essential to studying the mechanism underlying heterosis in improving drought tolerance of rice breeding. In this study, Dexiang074B (074B) and Dexiang074A (074A) served as maintainer lines and sterile lines. Mianhui146 (R146), Chenghui727 (R727), LuhuiH103 (RH103), Dehui8258 (R8258), Huazhen (HZ), Dehui938 (R938), Dehui4923 (R4923), and R1391 served as restorer lines. The progeny were Dexiangyou (D146), Deyou4727 (D4727), Dexiang 4103 (D4103), Deyou8258 (D8258), Deyou Huazhen (DH), Deyou 4938 (D4938), Deyou 4923 (D4923), and Deyou 1391 (D1391). The restorer line and hybrid offspring were subjected to drought stress at the flowering stage. The results showed that Fv/Fm values were abnormal and oxidoreductase activity and MDA content were increased. However, the performance of hybrid progeny was significantly better than their respective restorer lines. Although the yield of hybrid progeny and restorer lines decreased simultaneously, the yield in hybrid offspring is significantly lower than the respective restorer line. Total soluble sugar content was consistent with the yield result, so we found that 074A can enhance drought tolerance in hybrid rice.